Habitat suitability evaluation of Harpadon nehereus in nearshore of Zhejiang province, China - Jiang, Rijin; Sun, Haoqi; Li, Xiafang; Zhou, Yongdong; Chen, Feng; Xu, Kaida; Li, Pengfei; Zhang, Hongliang (Frontiers in Marine Science, 2022)
Coastal waters provide an important spawning and nursery ground for offshore marine organisms. To understand the suitable habitat and distribution of Harpadon nehereus, a key nearshore species, this study assessed the survey data of fishery resources and environment in Zhejiang’s nearshore fishery in Spring of 2017 to 2020. We used the generalized additive model (GAM) and random forests model (RF) to analyze the environmental factors affecting the selection of spawning habitats by H. nehereus and analyzed the suitable habitat characteristics of H. nehereus in nearshore fisheries. Our results indicate that H. nehereus is widely distributed in Zhejiang’s nearshore and that its density is higher in waters near islands and reefs. Among the relative importance scores of predictors calculated based on RF, seawater salinity is an important environmental factor affecting the distribution of H. nehereus in April (surface seawater salinity was 38.67% and bottom seawater salinity was 34.5%), followed by depth (34.19%), whereas the change in water temperature had no obvious effect on H. nehereus distribution. The suitable habitat characteristics of H. nehereus mainly include high salinity near a water depth of 40 m and a water area with sea bottom dissolved oxygen levels < 6 mg/L. The prediction results of the model indicate that the suitable habitat of H. nehereus is mainly located in the region near Zhoushan Islands in the north of the fishing grounds. Overall, these results may serve as a basis for determining the protection strategies of key nearshore species and enhancing fishery management units.